2022
DOI: 10.3390/cancers14133217
|View full text |Cite
|
Sign up to set email alerts
|

The Role of microRNAs in Multidrug Resistance of Glioblastoma

Abstract: Glioblastoma (GBM) is an aggressive brain tumor that develops from neuroglial stem cells and represents a highly heterogeneous group of neoplasms. These tumors are predominantly correlated with a dismal prognosis and poor quality of life. In spite of major advances in developing novel and effective therapeutic strategies for patients with glioblastoma, multidrug resistance (MDR) is considered to be the major reason for treatment failure. Several mechanisms contribute to MDR in GBM, including upregulation of MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 184 publications
0
7
0
2
Order By: Relevance
“…In another study, BDMC was used to reverse MDR in cisplatin-resistant non-small cell lung cancer by inhibition of CA916798 mRNA and protein and PI3K/AKT activities [ 61 ]. Despite advances and new strategies for treating GBM, MDR is a significant cause of failure for commonly used chemotherapeutic agents, including temozolomide (TMZ) [ 62 , 63 ]. Other causes include innate tumor cell resistance, inadequate drug concentration due to the blood–brain–tumor barrier, molecular heterogeneity, and clinical trials of new drugs in small groups [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study, BDMC was used to reverse MDR in cisplatin-resistant non-small cell lung cancer by inhibition of CA916798 mRNA and protein and PI3K/AKT activities [ 61 ]. Despite advances and new strategies for treating GBM, MDR is a significant cause of failure for commonly used chemotherapeutic agents, including temozolomide (TMZ) [ 62 , 63 ]. Other causes include innate tumor cell resistance, inadequate drug concentration due to the blood–brain–tumor barrier, molecular heterogeneity, and clinical trials of new drugs in small groups [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, miR-33b was lowly expressed in BC tissues and suppressed the EMT progress and invasion of BC despite targeting HMGA2, spalt-like transcription factor 4 (SALL4), and twist family bHLH transcription factor 1 (TWIST1) (94). Furthermore, acting as a negative regulatory factor, miR-143-5p could decrease VIM and CDH2 protein expression and increase CDH1 protein expression by directly targeting HMGA2 (95). Research that focused on the effects of modifications on miRNA has demonstrated that N6-methyladenosine modification of RNAs is crucial for cancer progression (96).…”
Section: Breast Cancermentioning
confidence: 99%
“…Based on the level of individual miRNAs, the miRNAs with the highest prognostic value for GBM were selected [ 72 ], indicating that that the diagnosis of GBM is also possible on the basis of the analysis of miRNA from the blood and cerebrospinal fluid of patients [ 73 , 74 , 75 ]. Functional analysis of individual GBM-specific miRNAs indicates that they can act as both oncogenes and tumor suppressors, are responsible for developing resistance to chemotherapy and radiotherapy, stimulate neo-angiogenesis and cell proliferation, and regulate the cell cycle and apoptosis [ 76 , 77 , 78 , 79 , 80 ] ( Table 2 ).…”
Section: Mirnas Expression In Gbmmentioning
confidence: 99%